Preliminary investigation of the effect of surcharge load and distance on non-homogenous man-made slope - Jestin Jelani; Syahmi Baharudin; Maidiana Othman; Mohd Nazrin Mohd Daud; Aina Syahirah Ahmad Ishak; Muhamad Azani Yahya (Penerbit Universiti Kebangsaan Malaysia, 2021)
Slope failure is a natural disaster that involves the movement of ground and rock under the influence of gravity. There are several factors influencing slope stability, including the excessive surcharge load imposed on the top of the slope. This study performs slope stability analysis to evaluate the performance of a non-homogenous man-made slope constructed on the UPNM campus. The methodology of this research comprises two parts. The first part is laboratory test, and the second part is simulation work. The laboratory tests conducted to determine the soil properties are sieve analysis, permeability test, and direct shear test. The limit equilibrium method using the SlopeW software is employed to determine the effect of imposing a gradually increasing surcharge load on the man-made slope from a varying distance. The value of Factor of Safety (FOS) and critical slip surface formation obtained using SlopeW were used to determine the maximum load carrying-capacity before failure. The results showed that the FOS decreased with an increasing surcharge load. However, the FOS increased as the distance of the load increase. Further analysis was carried out to enhance the stability of the slope. By reducing 40% of slope height, the stability of slope is increased to 44%. It is also suggested that no activity or development should be carried out on the slope crest to prevent slope failure occurrence in the future.